In situ growth induction of the corneal stroma cells using uniaxially aligned composite fibrous scaffolds. Issue 16 (23rd January 2015) - Zhang, Cong; Wen, Jihong; Yan, Jing; Kao, Yanbing; Ni, Zhiqiang; Cui, Xuejun; Wang, Hongyan
Abstract : An electrospun fibrous scaffold was fabricated and used in the in situ remediation of rabbits' corneal stromata. Abstract : Uniaxially aligned composite fibrous scaffolds of gelatin and poly-l -lactic acid (PLLA) were fabricated using electrospinning and the scaffolds were implanted into the corneal stroma layers of New Zealand white rabbits (NZWRs) to observe the in situ growth induction of the stroma cells. The effects on cell growth were evaluated by both apparent observation and pathological analysis. It was demonstrated that the scaffolds had a good compatibility with the corneal tissues and were nontoxic by observing the changes of the structure and the physiological activity of the corneal tissues around the scaffolds using a slit lamp and in vivo confocal images. The in vivo confocal images of the scaffolds implanted into the eyes of NZWRs show the process of the cells' ingrowth and the tissue regeneration, which indicated that the uniaxially aligned fibers could induce the polarized ingrowth of keratocytes which may provide the basis for clinical application to the in situ repair of corneal stromata.